2014
DOI: 10.1177/0146167214549540
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in Life as a Resource for Increasing Comfort With Ethnic Diversity

Abstract: Emerging demographic trends signal that White Americans will soon relinquish their majority status. As Whites' acclimation to an increasingly diverse society is poised to figure prominently in their adjustment, identifying sources of greater comfort with diversity is important. Three studies (N = 519) revealed evidence that purpose in life bolsters comfort with ethnic diversity among White adults. Specifically, dispositional purpose was positively related to diversity attitudes and attenuated feelings of threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Consistent with this work, white Americans have been found to reveal a preference for other white Americans both historically and in contemporary US society (Bobo et al 2012, Duckitt 2010, especially when such preferences are assessed relatively unobtrusively (Banaji & Greenwald 2013, Crosby et al 1980. For instance, although multiply determined, white Americans continue to show a preference for living in relatively segregated neighborhoods (Bobo et al 2012, Burrow et al 2014. Further, as the influence of explicit racial bias seems to be on the decline in many social arenas, recent theoretical and empirical work argues that it is everyday discrimination in the form of ingroup favoritism that maintains racial disparities, for instance, in employment (DiTomaso 2013) and many legal outcomes (Sommers & Marotta 2014).…”
Section: Social Identity Theorymentioning
confidence: 63%
“…Consistent with this work, white Americans have been found to reveal a preference for other white Americans both historically and in contemporary US society (Bobo et al 2012, Duckitt 2010, especially when such preferences are assessed relatively unobtrusively (Banaji & Greenwald 2013, Crosby et al 1980. For instance, although multiply determined, white Americans continue to show a preference for living in relatively segregated neighborhoods (Bobo et al 2012, Burrow et al 2014. Further, as the influence of explicit racial bias seems to be on the decline in many social arenas, recent theoretical and empirical work argues that it is everyday discrimination in the form of ingroup favoritism that maintains racial disparities, for instance, in employment (DiTomaso 2013) and many legal outcomes (Sommers & Marotta 2014).…”
Section: Social Identity Theorymentioning
confidence: 63%
“…When reminded of an increasingly diverse society, White Americans report threat to their sense of being a prototypical American (cueing low self‐concept fit; Danbold & Huo, ) and to their social inclusion (cueing low social fit; Plaut, Garnett, Buffardi, & Sanchez‐Burks, ). In other work, bolstering valued goals (which we argue might increase goal fit) can mitigate Whites' opposition to diversity (Burrow, Stanley, Sumner, & Hill, ).…”
Section: The Role Of Social Identity In Self‐segregation and An Asymmmentioning
confidence: 79%
“…Further, Kashdan and McKnight (2013) explored purpose as an intervention for those suffering from Social Anxiety Disorder (SAD): While purpose inductions helped those suffering from SAD to experience a greater sense of meaning in life and self-esteem, healthy controls did not see similar gains. Similarly, Burrow, Stanley, et al (2014) found that purpose was only helpful in alleviating threat when white participants were faced with the demographic trends pointing to a "majority minority" in the USA compared to all other groups combined-there was no relation between purpose and threat when participants believed they would remain the majority. Purpose may be limited in the sense that it is most helpful to those most in need and may not provide a boost for those who are already secure.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Importantly, there is evidence to suggest that individuals induced to think about purpose can experience similar positive outcomes to individuals with high levels of dispositional purpose (e.g., Burrow & Hill, 2013;Burrow, Stanley, Sumner, & Hill, 2014). Generally, these manipulations involve a writing task wherein participants describe their purpose in life.…”
Section: Purpose Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation